Employees’ Internal Factors Leading to Rule-breaking Acts at the Workplace - Ikhwanuddin, Rizky Yuli; Djunaidi, Zulkifli (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: The 2022 National Occupational Health and Safety (OHS) Profile in Indonesia shows that the human factor in safety is a factor that influences the risk of workplace accidents. The mining accidents statistical data in Indonesia, in which there was a 100% increase of workplace accidents in 2022, have given this industry an urgency to get a special attention to study risk-taking behavior at the workplace. At the organizational level, PT. XYZ (a mining contractor company in Indonesia) has internally measured its safety maturity level and is currently in calculative level, which indicates that the OHS management system has been implemented but the number of unsafe behaviors and unsafe conditions on site is still high. This paper explores quantitative results from research which aims to obtain an overview of employees’ internal factors leading to rule-breaking acts at the workplace. Methods: This paper uses cross-sectional design research with quantitative approach. Using stratified random sampling, a sample of 283 employees of PT. XYZ Site A participated in this study, ranging from managers, supervisors, and workers. Data were collected through a questionnaire with open-ended questions referring to a study from Safe Work Australia and analyzed quantitatively using statistical Chi-Square statistical test. Results: From the results of the Chi-Square test, the independent variables that have a value of Asymp. Sig. (2-sided) below 0.05 (95% CI) and lead to rule-breaking act at workplace are risk-taking behavior acceptance (0.018), normalizing minor accidents (0.002), and decision to take risk (0.000). Conclusion: Employees’ internal factors of risk-taking behavior acceptance, normalizing minor accidents, and decision to take risk have positive and significant effect on rule-breaking acts at the workplace. It is recommended that organizations implement a proper risk management with ALARP principle, safety empowering leadership, and safe behavior trainings to minimize rule-breaking acts at the workplace